ARTISTIC GAZE OF TWO PAPUAN CHOREOGRAPHERS: VISUAL PERSPECTIVES ROOTED IN THE ORAL TRADITIONS OF THE KAMORO AND ASMAT TRIBE - Ismar, Madia Patra; Pratiwi, Rahayu (UI Scholars Hub, 2020)
This article is based on the artistic practice of two Papuan choreographers trained in the Jakarta Institute of the Arts Dance Study Program. Both based their choreographies on their traditional roots which were presented as site specific performances in their respective villages. The choice of visuals and dramatic bodily expressions created by them, though a new dance design, was based on their deeply ingrained roots as indigenous Papuans. The roots called upon to be re-interpreted as choreography were based on the oral traditions they grew up with as part of their identity. The focus in this article is on the work by Martinus Akai from the Asmat tribe performed in 2013, and the work by Alfo Smith from the Kamoro Tribe performed in 2018. The purpose of this study is to understand the way Papuan choreographers ingrained in their cultural heritage re-imagine the traditions passed down from ancient times through their ancestors. The research done by the choreographers was in the context of revisiting the rituals and ancestral narratives and interpreting for a contemporary expression. The research done for this paper was based on discussions had with both the choreographers during the process of creating their individual work. Among the methods for collecting data by the choreographers for creating their work was field research, observations, interviews and personal memories experiencing their cultural heritage. The observations by the writers for this article were during the creating process in the studio and on site and viewing the end results both as presentations and site specific performances